Antimicrobial Sensitivity Pattern in the Mixed Intensive Care Unit in a Tertiary Care Hospital of Eastern Nepal - Keyal, Niraj Kumar; Shrestha, Mahendra; Ghimire, Partima Sigdel (Eastern Green Neurosurgery, 2020)
Background: Empirical antibiotics are used in the intensive care unit based on developing countries’ guidelines due to a lack of a bacteriological profile of individual ICU and institution policy. Therefore, this study was conducted to know the antibiogram of the intensive care unit and to make institution policy for antibiotic use in ICU.Materials and methods: It was a prospective descriptive cross-sectional study conducted in the mixed surgical and medical intensive care unit of a tertiary care hospital for one year in 625 patients. Various clinical samples were collected aseptically and organisms were identified by the cultural characteristics, morphology, gram stain, and different biochemical test. Antimicrobial susceptibility was done with a disc diffusion test. Data collection was done in a preformed sheet that included all tested antibiotic and demographic variables. Statistical analysis was done by using statistical package for the social sciences. The result was presented as frequency and percentage.Results: Out of 625 samples, 135(22%) showed growth in culture. Among them, 96(71%) and 39(29%) were gram-negative bacilli and gram-positive cocci respectively. The tracheal aspirate was the most common type of specimen which comprised 49(36.29%) isolates. The most common organism was Staphylococcus aureus which accounts for 27(20%) isolates, followed by Acinetobacter baumanni 25(18.51%), Klebsiella pneumoniae 22(16.29%) and Pseudomonas aeurignosa 21(15.55%). The incidence of multidrug-resistant and extended drug resistance was 44(32.5%) and 45(33%) respectively. Meanwhile, the incidence of methicillin-resistant staphylococcus aureus was 70%. However, in the case of Acinetobacter baumannii and Enterobacteriaceae, all were sensitive to polymyxin B and meropenem.Conclusion:Antibiotics should be prescribed based on the antibiogram of individual intensive care units that can decrease antibiotic resistance. Polymyxin B and meropenem can be prescribed for gram-negative bacilli and vancomycin for Staphylococcus aureus.